Generic dimensions of teaching quality: the German framework of Three Basic Dimensions - Praetorius, Anna-Katharina; Klieme, Eckhard; Herbert, Benjamin; Pinger, Petra (ZDM, 2018)
In this paper, we argue that classroom management, student support, and cognitive activation are generic aspects of classroom teaching, forming Three Basic Dimensions of teaching quality. The conceptual framework was developed in research on mathematics instruction but it is supposed to generalize across subjects. It is based on general theories of schooling and teaching as well as established theories and research traditions from educational psychology. Although used frequently in German-speaking countries, no comprehensive overview of the theoretical foundation as well as the existing evidence regarding the framework, including its strengths and weaknesses, exists so far. The present paper therefore presents first an overview of the theoretical rationale of the framework. Second, it gives an overview of differences and commonalities in the operationalizations of the Three Basic Dimensions in different studies, including a comprehensive set of sub-dimensions. Third, evidence on the reliability and validity of the dimensions is reviewed, with good results for reliability and mixed results for predictive validity. Fourth, an analysis of three mathematics lessons using observer ratings illustrates how the framework of the Three Basic Dimensions can be used for investigating instructional quality. Finally, strengths and limitations of the framework for capturing instructional quality are discussed and we elaborate on the framework's potential for further development. (DIPF/Orig.).